Psychiatric Disorders among Rural House Wife’s: Exploring Gender Differences in Psychiatric Disorders among Rural Housewives (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Gender is a critical determinant of mental health and mental illness. The patterns of psychological distress and psychiatric disorder among women are different from those seen among men. Women have a higher mean level of internalizing disorders while men show a higher mean level of externalizing disorders. Gender differences occur particularly in the rates of common mental disorders wherein women predominate. Differences between genders have been reported in the age of onset of symptoms, clinical features, frequency of psychotic symptoms, course, social adjustment, and long-term outcome of severe mental disorders. Women who abuse alcohol or drugs are more likely to attribute their drinking to a traumatic event or a stressor and are more likely to have been sexually or physically abused than other women. Girls from nuclear families and women married at a very young age are at a higher risk for attempted suicide and self-harm.